COMPARISON OF INTRAOCULAR PRESSURE AND HAEMODYNAMIC RESPONSES TO INSERTION OF THE I - GEL AND ENDOTRACHEAL TUBE IN ELECTIVE OPHTHALMOLOGICAL SURGERIES - Abbas, Sana; Rafique, Aisha; Dilshad, Dr; Abbas, Beenish (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare I–Gel versus endotracheal tube effects on hemodynamic stability and intraocular pressure in patients undergoing elective ophthalmological surgeries. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Nov 2019 to Oct 2020. Methodology: A total of 108 patients undergoing elective ophthalmological surgeries under general anesthesia from both genders, age range between 18-45 years, American Society of Anesthesiologists status I or II were included. General anesthesia given following standard procedures and monitoring. Heart rate, Systolic & Diastolic blood pressure monitored and intraocular pressure measured in each eye with Reichert ton open at baseline, upon insertion of airway device and 5 minutes after insertion. Results: Total 108 patients enrolled in the study with a mean age of 37.74 ± 6.0 years and age-range of 18-45. Heart rate at Insertion in I-Gel group was 78.14 ± 3.41 beats per minute whereas in intubated group was 97.20 ± 2.84 beats per minute, mean systolic blood pressure at insertion in group A and B was 115.28 ± 5.3 and 130.44 ± 2.81mm of Hg respectively. Intraocular pressure at insertion right eye in group A and B was 12.04 ± 0.48 and 17.98 ± 0.42 mm of Hg respectively. Intraocular pressure at insertion left eye in group A was 12.12 ± 0.45 whereas in group B was 17.95 ± 0.38mm of Hg (p-value=0.001). Conclusion: I–Gel provides better hemodynamic profile and intraocular pressure stability when compared with endotracheal tube.